2021
DOI: 10.3390/molecules26030567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cetuximab-Conjugated Gold Nanoparticles on the Cytotoxicity and Phenotypic Evolution of Colorectal Cancer Cells

Abstract: Epidermal growth factor receptor (EGFR) is estimated to be overexpressed in 60~80% of colorectal cancer (CRC), which is associated with a poor prognosis. Anti-EGFR targeted monoclonal antibodies (cetuximab and panitumumab) have played an important role in the treatment of metastatic CRC. However, the therapeutic response of anti-EGFR monoclonal antibodies is limited due to multiple resistance mechanisms. With the discovery of new functions for gold nanoparticles (AuNPs), we hypothesize that cetuximab-conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Our previous study has demonstrated that higher SERS activity could be obtained by using AuNPs (60 nm) as compared to smaller AuNPs (i.e., 25 and 40 nm). [ 23 ] Meanwhile, 60 nm AuNPs are less prone to aggregation compared to larger AuNPs at size of 80 nm. [ 23 ] Thus, AuNPs (60 nm) were used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study has demonstrated that higher SERS activity could be obtained by using AuNPs (60 nm) as compared to smaller AuNPs (i.e., 25 and 40 nm). [ 23 ] Meanwhile, 60 nm AuNPs are less prone to aggregation compared to larger AuNPs at size of 80 nm. [ 23 ] Thus, AuNPs (60 nm) were used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Meanwhile, 60 nm AuNPs are less prone to aggregation compared to larger AuNPs at size of 80 nm. [ 23 ] Thus, AuNPs (60 nm) were used in this study. The size and morphology of AuNPs were investigated with transmission electron microscopy (TEM), where the quasi‐spherical shape of as‐prepared AuNPs was observed (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, enhanced therapeutic efficacy of cetuximab-functionalized nanoaprticles has been reported in different nanomedicine systems. [455][456][457][458][459][460] For example, Landgraf et al constructed porous silicon nanoparticles modified by chemotherapeutic drug camptothecin (CPT) and anti-EGFR cetuximab for cancer-targeted delivery. [458] CPT-loaded porous silicon nanoparticles bearing active targeting capacity contributed to the inhibition of orthotopic primary tumor growth, an increase in survival rate, and notable reduction in humanized tissue-engineered bone constructs and murine liver, lung, and bone metastases.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Results showed the cytotoxicity of cetuximab-AuNPs to cancer cells, with NPs mainly possessing a size of 60 nm. It was also possible to analyze the change in the expression of biomarkers on the surface of the cancer cell, where, after treatment with cetuximab-AuNPs, there was a greater expression of epithelial cell markers: epithelial cell adhesion molecule (EpCAM), melanoma cell adhesion molecule (MCAM) and human epidermal growth factor receptor-3 [ 107 ].…”
Section: Nanoparticles As Drug Delivery Systemsmentioning
confidence: 99%